Evaluation of the in vitro antifungal activity of curcumin associated to photodynamic therapy on species of the Complex Fusarium solani and Fusarium oxysporum (Research, Society and Development, 2023)
The Fusarium genus is among the pathogens that cause onychomycosis (OM), and is included among the non-dermatophyte filamentous fungi, with the Fusarium solani and Fusarium oxysporum species standing out. Among the therapeutic options for OM, Photodynamic Therapy (PDT) stands out, which, associated with Curcumin (CUR), is an interesting proposal in the antifungal context. The aim was to standardize and evaluate the antifungal activity of PDT+CUR on clinical isolates of Fusarium spp. The CUR was supplied by the UEM Photodynamic Research Center, and the Fusarium strains were obtained from samples from the Clinical Analysis Teaching and Research Laboratory, approved by the ethics committee (nº2.748.843). Blue LED (440nm to 460nm) was used for irradiation, and CUR was used at concentrations of 50-0.09µmol/L. The inoculum of the isolates was standardized at a concentration of 105 CFU/mL. After incubation for 10, 20 and 30 minutes in the dark with CUR, the plates were irradiated at doses of 15, 30 and 45 J/cm2. The antifungal action of PDT+CUR was assessed qualitatively and quantitatively. The results were analyzed using the GraphPad Prism 5.0® software, with One-Way Analysis of Variance (ANOVA) and Tukey's test. The best antifungal combination of incubation time and fluence of PDT+CUR was 10 minutes for pre-irradiation and 30 J/cm2 irradiation. These conditions were able to inactivate 75% of the clinical isolates tested from a concentration of 0.78µmol/L. The results of this study show that PDT+CUR was fungicidal and promising, encouraging further research in the field of medical mycology.